Urinary soluble (pro)renin receptor excretion is associated with urine pH in humans. - Nobukazu Sasaki (PLoS ONE, 2021)
The (pro)renin receptor [(P)RR] binds to renin and its precursor prorenin to activate the tissue renin-angiotensin system. It is cleaved to generate soluble (P)RR and M8-9, a residual hydrophobic truncated protein. The (pro)renin receptor also functions as an intracellular accessory protein of vacuolar-type H+-ATPase, which plays an essential role in controlling the intracellular vesicular acid environment. Thus, in the kidney, (P)RR may play a role in transporting H+ to urine in the collecting duct. Although blood soluble (P)RR has been recognized as a biomarker reflecting the status of the tissue renin-angiotensin system and/or tissue (P)RR, the significance of urinary soluble (P)RR excretion has not been determined. Therefore, this study aimed to investigate the characteristics of urinary soluble (P)RR excretion. Urinary soluble (P)RR excretion was measured, and its association with background factors was investigated in 441 patients. Relationships between changes in urine pH due to vitamin C treatment, which reduce urine pH, and urinary soluble (P)RR excretion were investigated in 10 healthy volunteers. Urinary soluble (P)RR excretion was 1.46 (0.44-2.92) ng/gCre. Urine pH showed a significantly positive association with urinary soluble (P)RR excretion, independent of other factors. Changes in urine pH and urinary soluble (P)RR excretion due to vitamin C treatment were significantly and positively correlated (ρ = 0.8182, p = 0.0038). These data showed an association between urinary soluble (P)RR excretion and urine pH in humans, suggesting that (P)RR in the kidney might play a role in urine pH regulation.